In silico Study of Toll-Like Receptor 4 Binding Site of FimH from Uropathogenic Escherichia coli - Mehri Habibi; Mohammad Reza Asadi Karam; Saeid Bouzari (Pasteur Institute of Iran, 2014)
Introduction : The innate immune system as the first line of defense against the pathogens recognizes pathogen-associated molecular patterns (PAMPs) by Toll-Like Receptors (TLRs). Interaction of bacterial PAMPs by TLRs results in activation of innate and acquired immunity. FimH adhesin, a minor component of type 1 fimbriae encoded by Uropathogenic Escherichia coli (UPEC) is a PAMP of TLR4 that stimulates the innate immunity against infections. The FimH involves N-terminal and C-terminal domains. Detailed information about the TLR4 interaction with FimH is lacking. Methods: In this study, we evaluated interaction between TLR4 and whole FimH and two domains of FimH using computational methods. Two truncated forms of FimH that included N- terminal and C- terminal truncated forms were selected from PDB. Molecular docking analysis of TLR4 against FimH was done using HEX docking tool. The molecular interaction plot between TLR4 and FimH was generated Dimplot in LIGPLOT software (v. 4.5.3). Results: Based on the total free energy, C- terminal truncated form had the best interaction tendency to the receptor. Dimplot analysis showed that there are 11 intermolecular hydrogen bonds in the TLR4 and C- terminal truncated form of FimH complex. Conclusion: The high affinity of C- terminal truncated form to TLR4 suggests that this portion of FimH has important effect on the adjuvant activity and innate immune response and could utilize as adjuvant for vaccine application against microbial infections and cancers. J Med Microbiol Infec Dis, 2014, 1 (2): 5 pages.